The Recruitment of Migrant Workers in the Food Service Industry in Malaysia. A Study of Old Town White Coffee and Pappa Rich Kopitiam - Yee, Yeo Sing; Yuen, Joyce Leu Fong (International Journal of Business, Economics and Management, 2014)
In the recent decades, the process of globalization has increased the mobility of labor and spurred rapid international migration across borders. As one of the major labor importers in Asia, the government of Malaysia is committed to reduce the number of migrant labors to 1.5 million by 2015. Though many researches have been conducted to study the employment effects of migrant workers towards the local labor economy, this research aims to examine the factors which lead to the recruitment of migrant workers in the café segment of food service industry in Malaysia, specifically Old Town White Coffee and Pappa Rich Kopitiam (Café) in Klang Valley, Malaysia. Four main factors are being studied in this research, namely the lower wages; acceptability of workers towards poor employment conditions; flexibility of employees at work and better work ethics of foreign labors. The recruitment of migrant workers is said to be motivated by three main factors: lower wages, acceptability of workers towards employment conditions and better work ethics of the foreign workforce. In addition, the flexibility of workers is proven to have no significant relationship with the recruitment of migrant workers in this sector.